A metal-free biaryl coupling reaction activated by a sulfonium salt. Issue 22 (2nd October 2018) - Higuchi, Kazuhiro; Tago, Takuhiro; Kokubo, Yusuke; Ito, Motoki; Tayu, Masanori; Sugiyama, Shigeo; Kawasaki, Tomomi
Abstract : A metal-free biaryl coupling reaction of phenol or aryl ethers mediated by a sulfonium salt formed from diphenyl sulfoxide and trifluoromethanesulfonic anhydride has been developed. The method is a rapid, one-pot reaction, leaving no traces of the sulfonium moiety in the product. Abstract : An intermolecular biaryl coupling reaction of phenol derivatives activated by a sulfonium salt formed from diphenyl sulfoxide and trifluoromethanesulfonic anhydride has been developed. The method is a rapid, one-pot reaction leaving no trace of the sulfonium moiety in the coupling products. Tri-substituted phenyl ethers also gave coupling products in moderate yields.